Emergence of high colistin resistance in carbapenem resistant Acinetobacter baumannii in Pakistan and its potential management through immunomodulatory effect of an extract from Saussurea lappa - Ahsan, Umaira; Mushtaq, Fizza; Saleem, Sidrah; Malik, Abdul; Sarfaraz, Hira; Shahzad, Muhammad; Uhlin, Bernt Eric; Ahmad, Irfan (Frontiers in Pharmacology, 2022)
Carbapenem resistant Acinetobacter baumannii has emerged as one of the most difficult to treat nosocomial bacterial infections in recent years. It was one of the major causes of secondary infections in Covid-19 patients in developing countries. The polycationic polypeptide antibiotic colistin is used as a last resort drug to treat carbapenem resistant A. baumannii infections. Therefore, resistance to colistin is considered as a serious medical threat. The purpose of this study was to assess the current status of colistin resistance in Pakistan, a country where carbapenem resistant A. bumannii infections are endemic, to understand the impact of colistin resistance on virulence in mice and to assess alternative strategies to treat such infections. Out of 150 isolates collected from five hospitals in Pakistan during 2019-20, 84% were carbapenem resistant and 8 % were additionally resistant to colistin. There were two isolates resistant to all tested antibiotics and 83% of colistin resistant isolates were susceptible to only tetracycline family drugs doxycycline and minocycline. Doxycycline exhibited a synergetic bactericidal effect with colistin even in colistin resistant isolates. Exposure of A. baumannii 17978 to sub inhibitory concentrations of colistin identified novel point mutations associated with colistin resistance. Colistin tolerance acquired independent of mutations in lpxA, lpxB lpxC, lpxD and pmrAB supressed the proinflammatory immune response in epithelial cells and the virulence in a mouse infection model. Moreover, the oral administration of water extract of Saussuria lappa, although not showing antimicrobial activity against A. baumannii in vitro, lowered the number of colonizing bacteria in liver, spleen and lung of the mouse model and also lowered the levels of neutrophils and interleukin IL-8 in mice. Our findings suggest that the S. lappa extract exhibits an immunomodulatory effect with potential to reduce and cure systemic infections by both opaque and translucent colony variants of A. baumannii.